Up-to-date approaches to treatment of the functional constipation at children - V. F. Privorotsky; N. Ye. Luppova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present diagnostic criteria of constipation of functional origin in children and to systematize approaches to medical programs development.Original positions of the review. Functional constipation contributes 95% of all cases of constipation at children. According to ICD-10, in the respective section, irritable bowel syndrome (IBS) and functional constipation itself are traditionally distinguished. RomeIII criteria adjust diagnostic principles of these diseases. In pediatric practice it is important to distinguish hypertonic and hypotonic constipations. In medical programs significant place is given to laxatives, especially in cases of sub- or decompensated variants of constipation. Of them Forlax® preparation on the basis of macrogoal 4000 (polyethyleneglycol 4000) with potential of prescription of the latter from 6-month’s age deserves attention. In the literature there are data indicating safety and high performance of this pharmaceutical agent.Conclusion. Rome criteria of IBS are applicable only in relation to children of middle and senior school age. At drawing up medical programs for children with functional constipation, it is advisable to take into account its type (spasmodic or hypotonic), degree of compensation, age of a child. At prescription of laxative agents it is necessary to choose drugs with osmotic mechanism of action.